Flashcards Improve Junior High Students Vocabulary Achievement: Kartu flash meningkatkan pencapaian kosakata siswa SMP. - Utari, Meralda Dwi; Mandarani, Vidya (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines the use of flashcards in English vocabulary instruction for seventh-grade students. General Background: Vocabulary mastery is a fundamental component of English language proficiency and supports listening, speaking, reading, and writing skills. Specific Background: In Indonesian junior high schools, students often experience difficulties in retaining newly learned vocabulary due to limited use of engaging learning media. Knowledge Gap: Although digital flashcards have been widely studied, limited attention has been given to handmade flashcards supported by AI-generated images in low-technology classroom contexts. Aims: This study aims to determine whether flashcard media improves students’ English vocabulary acquisition and learning interest at SMP Muhammadiyah 8 Tanggulangin. Results: Using a pre-experimental One Group Pretest-Posttest Design with 20 students, the findings reveal an increase in mean scores from 71.00 to 75.75, with a paired sample t-test significance value of 0.000 (p < 0.05), indicating a statistically significant difference. Novelty: The study highlights the integration of AI-generated images into handmade flashcards as a practical low-cost instructional strategy. Implications: Flashcards can be integrated into English language teaching to support vocabulary retention, active participation, and meaningful repetition in junior high school contexts. Keywords: Flashcards, Vocabulary Mastery, English Language Learning, Junior High School Students, Pre-experimental Design Key Findings Highlights Mean scores increased significantly after classroom intervention. Statistical testing confirmed measurable learning gains. Visual repetition supported classroom participation and retention.